The first delinquency prevention experiment: a socio-historical review of the origins of the Cambridge-Somerville Youth Study’s research design - Welsh, Brandon (Journal of experimental criminology, 2019)
Begun in 1939, the Cambridge-Somerville Youth Study (CSYS) is recognized as the first delinquency prevention experiment and the earliest example of a longitudinal-experimental study with criminological outcomes. This paper aims to develop a historical understanding of the origins of the study’s research design.